Firms and Collective Reputation: The Volkswagen Emission Scandal as a Case Study - Ruediger Bachmann; Gabriel Ehrlich; Dimitrije Ruzic (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper uses the 2015 Volkswagen emissions scandal as a natural experiment to provide causal evidence that group reputation externalities matter for firms. Our estimates show statistically and economically significant declines in the U.S. sales and stock returns of, as well as public sentiment towards, BMW, Mercedes-Benz, and Smart as a result of the Volkswagen scandal. In particular, the scandal reduced the sales of these non-Volkswagen German manufacturers by approximately 76,000 vehicles over the following year, leading to a loss of approximately 3.7 billion of revenue. Volkswagen's malfeasance materially harmed the group reputation of “German car engineering” in the United States.
Keywords: D12; D90; F23; L14; L62; 330; automobiles; collective reputation; country reputation; difference-in-differences; event study; Google trends; firm reputation; natural experiment; reputation externalities; Twitter sentiment; Volkswagen emissions scandal